Forsythiaside A Reduces Acetaminophen Hepatotoxic Metabolism by Inhibiting Pregnane X Receptor - Sisi Pu; Yangyang Pan; Zuoyang Wang; Huimin Liu; Jianhui Zhang; Qian Zhang; Meng Wang (Molecules)
Overdose intake of acetaminophen (APAP) causes liver injury involving hepatic drug metabolism and activation of oxidative stress pathways, and forsythiaside A (FA) has hepatoprotective pharmacological activity, but knowledge of the mechanism of FA treatment for APAP liver injury is still lacking the literature. In this study, we investigated the effects of FA on the pregnane X receptor (PXR) by molecular docking and reporter gene assays. In addition, we explored the effects of FA on oxidative stress, endoplasmic reticulum stress (ERS), apoptosis, and hepatic pathology by interfering with PXR in ex vivo and in vivo models. The results showed that FA decreased the PXR protein expression level and effectively reduced the oxidative stress level in the APAP model. In addition, FA reduced the expression of ERS pathway ProteinkinaseR-likeERkinase (PERK)-translation initiation factor 2 (eIF-2α)-activating transcription factor 4 (ATF4) by inhibiting PXR, and at the same time, decreased the expression of apoptotic proteins C/EBP homologous protein (CHOP), Bax, Caspase 3, and Caspase 7, and elevated the expression of apoptosis-suppressing protein Bcl-2, which ultimately treated the hepatic pathology injury of APAP in mice. The present study confirmed that FA improved APAP metabolism by inhibiting PXR-mediated CYP1A2 and CYP3A11 and alleviated APAP-induced hepatic impairment by inhibiting hepatic oxidative stress, ERS, and apoptosis.